Assessment practices in biosciences: university students' and teachers' views - Matimolane, Mapula Nkgau (My University, 2016)
This doctoral thesis investigates highly emotive and topical aspects of student learning in higher education namely, assessment and feedback. The study deals with the complexities and barriers to using learning-oriented assessment approaches to equip students with skills needed to thrive within the uncertainty, demands and challenges of rapidly changing societies. In the current research literature, views about assessment, and in particular formative assessment, are diverse and in some instances contradictory. The argument I make in this thesis is that assessment is situated within a local context, comprised of students and their teachers, which is regulated by disciplinary, professional and institutional traditions, expectations and needs. This research study was impelled by the realisation that most research into pedagogical views held by teachers and their students in higher education has examined them in isolation of each other. In recognition of this disparity in the literature, a more comprehensive study on teachers' and students’ views, expectations, and experiences of assessment was undertaken in the South African context. The study was conducted at a research-intensive university and investigated the aforementioned assessment aspects in students and teachers involved in second year compulsory bioscience courses. Using an exploratory, interpretative, mixed method research approach, data were collected through a combination of interviews, questionnaires and document analysis. An in-depth examination of documents from the selected courses, including students’ marked work, provided evidence of assessment and feedback practices experienced by the students registered in the courses. Teachers were interviewed about their assessment practices and their rationale for using these practices. Students' views and their reactions to assessment and feedback were ascertained through questionnaires and interviews. Interpretations that emerged from using a socio-cultural-historical theoretical lens were helpful in understanding the factors that present challenges to the implementation of learning-oriented assessment approaches. From the characterisation of assessment environments based on learning-oriented assessment principles it was apparent that there was limited active involvement of students in the process. The data highlighted a complex array of factors influencing teachers’ conceptions of assessment and subsequently their practices. Significant about the study was the identification of the effects of existing course level assessment cultures and histories on teachers’ assessment practices. Program and course factors had more influence on teachers’ practice than their subject expertise, pedagogical beliefs and values. The main highlights emerging from the study were the multiplicity of students’ and teachers’ views of assessment and feedback with a number of convergent and divergent perspectives. Notably, the cause of dissonance between academics and students stems from the tension between the competing needs of facilitating students’ independence and the desire to give them detailed corrective feedback. This dissonance translated into varied emotional responses to feedback from students. Although the focus of the study was on the comparison between students’ and teachers’ understanding of assessment, the preponderance of students’ emotional reactions to assessment feedback that emerged offered an important insight into an unpredicted social-relational dimension of assessment. My original contribution to research knowledge is the generation of the Assessment-Systems-for-Practice (ASP) framework, a reflection and methodological tool for investigating and analysing assessment practices. This framework provides a holistic way of dealing with the complex nature of assessment in higher education. The framework thus has implications for assessment design that would take into consideration cognitive, structural and social-relational dimensions, and its use could have a positive impact on teachers’ individual assessment practices.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy Johannesburg, South Africa June, 2015
Keywords: Life sciences.; Life sciences--Study and teaching.; Science teachers--South Africa.; University students--South Africa.